2013
DOI: 10.1063/1.4842896
|View full text |Cite
|
Sign up to set email alerts
|

Thermal resistance between crossed carbon nanotubes: Molecular dynamics simulations and analytical modeling

Abstract: A nonequilibrium molecular dynamics (MD) method is used to calculate the thermal resistance between crossed carbon nanotubes (CNTs). The thermal resistance is predicted to be of the order of 10 9-10 11 K/W. The effects of the crossing angle, nanotube length, and initial nanotube spacing on the thermal resistance are studied in detail with the fixed boundary condition applied in the axial direction of each CNT. The thermal resistance is found to increase with the increasing crossing angle while decrease with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 42 publications
4
23
0
Order By: Relevance
“…We employed the NEMD method [38][39][40][41] and constructed a series of simulation systems, as illustrated in figure 1. Figure 1a depicts the simplest system having one variable-width-constriction, constructed by introducing two linear vacancy defects in a pristine graphene sheet.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…We employed the NEMD method [38][39][40][41] and constructed a series of simulation systems, as illustrated in figure 1. Figure 1a depicts the simplest system having one variable-width-constriction, constructed by introducing two linear vacancy defects in a pristine graphene sheet.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…where R K is the Kapitza interface thermal resistance across the SWCNTs and matrix, and its value is given as 5 Â 10 À8 m 2 K=W [31,32].…”
Section: Thermal Conductivity Of the Unit Cell Containing All The Filmentioning
confidence: 99%
“…Xu and Buehler [55] concluded that the length effect was small enough to disregard for lengths between 25 and 75 nm. Hu and Cao [69] investigated the thermal resistance at the interface between crossed CNTs with lengths less than 9 nm. Similarly to our observations, their results show a decrease of the thermal resistance with increasing CNT length for shorter CNTs, but suggest saturation of the length dependence near L T ≈ 9 nm.…”
Section: B Effect Of Cnt Lengthmentioning
confidence: 99%
“…With complete characterization of the physical system being studied, the MD simulation method allows for a systematic study of the dependence of CNT-CNT conductance on parameters that may be modified to optimize the thermal properties of CNT-based materials. The simulations have provided important insights into the mechanisms responsible for the inter-tube heat transfer between parallel CNTs [53][54][55][56] or CNTs crossing each other at an angle [51,58,[67][68][69]. While the variation of the values of the conductance per unit area of the inter-tube contacts by more than two orders of magnitude [56] suggests a strong and complex dependence of the inter-tube conductance on the geometry and density of the contacts, the design of a general heat transfer model that would account for this dependence is hampered by the differences in computational methods, interatomic potentials, definitions of the contact area, length and type of the CNTs used in the simulations, etc.…”
Section: Introductionmentioning
confidence: 99%